A Cost-Benefit Analysis of a Public Labelling Scheme of Fish Quality - Max Nielsen; Frank Jensen; Eva Roth (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2004)
The purpose of this paper is to introduce a new method capable of evaluating the economic welfare for quality graded fish products using the hedonic price method for plaice in Denmark. Today no labelling scheme exists for the final consumers of different qualities of fish. A scheme does only exist at the first hand market. On this basis, a general applicable theoretical and empirical method is developed to compare the costs and benefits of the hypothetical choice between the total absence of labelling and the presence of a public label-ling scheme, which fully inform consumers on the quality and simultaneously allow the producers to differentiate prices between quality grades. It is shown that the economic welfare associated with a public labelling scheme is at mini-mum 263,000 euro. Sensitivity analysis shows that this result is robust. The pol-icy implication is that a public labelling scheme should not be implemented as the demand and cost functions have low elasticities, implying that the welfare gain is low.
Keywords: L11; Q21; Q22; 330; Co-integration; fish quality; hedonic pricing; public labelling scheme; welfare; Fische; Produktqualität; Hedonischer Preisindex; Kointegration